2001
DOI: 10.1002/jmri.1054
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 3He MR lung ventilation imaging in asthmatics: Preliminary findings

Abstract: Asthma is a disease characterized by chronic inflammation and reversible obstruction of the small airways resulting in impaired pulmonary ventilation. Hyperpolarized 3 He magnetic resonance (MR) lung imaging is a new technology that provides a detailed image of lung ventilation. Hyperpolarized 3 He lung imaging was performed in 10 asthmatics and 10 healthy subjects. Seven asthmatics had ventilation defects distributed throughout the lungs compared with none of the normal subjects. These ventilation defects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
345
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(364 citation statements)
references
References 16 publications
14
345
1
2
Order By: Relevance
“…Similar measures, combined with quantitative measures of airway lumen size and wall thickness, may also allow measurement of gas trapping and airway narrowing associated with other obstructive lung diseases such as asthma (24). Although HR CT can provide quantitative assessment and diagnosis of the anatomical features of lung diseases, HP MRI has the means to perform a range of functional measures including regional ventilation (25)(26)(27), and V A /Q mapping (28,29), while also providing images of regional microstructure-in some applications at length scales similar to or smaller than those depicted on CT (30,31)-and all of these measures are performed without ionizing radiation.…”
Section: Lung Imaging Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar measures, combined with quantitative measures of airway lumen size and wall thickness, may also allow measurement of gas trapping and airway narrowing associated with other obstructive lung diseases such as asthma (24). Although HR CT can provide quantitative assessment and diagnosis of the anatomical features of lung diseases, HP MRI has the means to perform a range of functional measures including regional ventilation (25)(26)(27), and V A /Q mapping (28,29), while also providing images of regional microstructure-in some applications at length scales similar to or smaller than those depicted on CT (30,31)-and all of these measures are performed without ionizing radiation.…”
Section: Lung Imaging Techniquesmentioning
confidence: 99%
“…In particular, ventilation imaging using HP MRI in the study of asthma has shown the ability to detect regional patterns of airway closure in moderate to severe disease (Fig. 2) (26) before and after inhalation of albuterol (67) and in mild asthma after inhaled corticosteroid withdrawal (68). Similar studies directly comparing quantitative CT measures to HP He-3 MRI ventilation in COPD and smokers (69), and bronchiolitis obliterans (BO) in lung transplant (70,71) suggest similar sensitivity and regional specificity for detection of obstructive lung disease using the two imaging techniques.…”
Section: Ventilation Imaging (Spin Density)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, assessment of regional lung ventilation using hyperpolarized noble gas has emerged as an imaging technique for evaluating patients with lung disease, such as tumor, emphysema, bronchiectasis, cystic fibrosis, and asthma (17)(18)(19)(20)(21)(22)(23)(24). Compared to O 2 -enhanced lung MRI (25,26), which has the advantage of needing no special equipment, 3 He MRI provides high SNR and contrast-to-noise ratio (CNR), with image intensity directly proportional to the local concentration of inhaled 3 He.…”
mentioning
confidence: 99%
“…The latter technique has shown a high signal-to-noise ratio (SNR), and permits the visualization of pulmonary arteries beyond the subsegmental branches. On the other hand, assessment of regional lung ventilation with hyperpolarized noble gas has emerged as an imaging technique for evaluating lung diseases, including tumors, emphysema, bronchiectasis, cystic fibrosis, and asthma (16)(17)(18)(19)(20)(21)(22)(23). A promising MR technique for visualizing the air spaces of the lung is the use of 3 He gas as a contrast agent.…”
mentioning
confidence: 99%